Development of Teaching Material for Short Story Writing Experience Based on 7th Grade Students of Junior High School 2 Kejuruan Muda - Dinda Khairun Nazila; Abdurahman Adisaputera; Amrin Saragih (BIRCU, 2020)
This study aims to develop teaching materials for writing short stories based on experience to facilitate students in writing short text. The learning approach offered by researchers is considered appropriate for writing short text material because it can help students to easily express their ideas in writing short stories by linking the material with the context of their daily lives. In addition, experience is the best teacher because from experience one can learn. Experience is a memory that is recorded and stored as a story that forms a filter of perception that ultimately guides behavior. The results of this study indicate that the effectiveness of teaching short story writing lessons based on experiences developed for 7th grade student of junior high school 2 Kejuruan Muda was stated to be more effective than student handbooks. The results of the acquisition of student learning outcomes before and after using teaching materials have increased quite significantly by 8.28. The average score of students before (pretest) using teaching materials learning experiences writing short stories based on experience 74.43 and the average value of post (testing) using teaching materials learning writing short stories based on experience 82.71.